Perancangan Aplikasi Augmented Reality 3D Sebagai Media Pembelajaran Rumah Adat Indonesia Dengan Algoritma FAST Corner di SDI Al-Munir Bekasi - Abdillah Prayoga Widyanto; Dwipa Handayani; Mayadi (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
Elementary school students still tend to be less interested in learning local culture, one of which is the variety of traditional houses in Indonesia. Students are more interested in global culture that is trending. The main reason is because the learning process that applies is still conventional and monotonous. The teaching methods that are carried out are only delivered verbally and through written media, resulting in low student involvement in the learning process. Many areas that have cultural heritage are at risk of losing valuable cultural assets due to limited interest and preservation efforts. Digital transformation allows for the creation of new innovations in the scope of education. Augmented reality technology can be used as a bridge to connect students with local cultural diversity. AR technology designed on mobile devices is an ideal medium to motivate the younger generation to maintain the sustainability of local culture in a modern way and in accordance with a digital lifestyle. The purpose of this study is to explore the use of 3D Augmented Reality technology collaborated with the FAST corner algorithm in the learning process as an effort to increase student interest in understanding the forms of traditional houses in Indonesia. The development of a waterfall system is a method in developing Android-based applications by utilizing Unity 3D programming. This research produces an Android-based application to recognize various forms of traditional houses in Indonesia which will be applied to 3rd grade elementary school students so that they can experience a more interactive learning experience.